A Novel Approach To Enhance The Qos Of Wireless Sensor Networks (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Wireless sensor networks (WSNs) has acquired more attention because of applications in various fields. The sensors have limited power sources as they cannot be replaced because of hostile nature. In this study, Genetic Algorithm (GA) based approaches for routing and clustering in WSNs have been proposed.  The significant purpose of the process is to enhance lifetime of sensor and Quality of Service (QoS). The results illustrate that proposed algorithms such as LECR-GA or NLCR-GA works better than the existing algorithm with respect to several performance metrics such as number of packets, energy consumption acknowledged by the base station.